PENGARUH PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI PASCA GEMPA BUMI/TSUNAMI DI KABUPATEN ACEH BARAT - Yayuk Eko Wahyuningsih; Yenny Ertika; Leli Putri Ansari (Universitas Teuku Umar, 2018)
The magnitude of the target acceptance of the various components in the original blood income (PAD) greatly affects the realization value of the The better PAD an area then the economic growth is rising. The increasing revenue of the local area will also affect the economic growth rate of an area, so it is happening in West Aceh district. This research aims to analyse the influence of indigenous revenue on the area of economic growth after the earthquake/tsunami in West Aceh Regency period 2005-2017. The data used is secondary data that is sourced to the Central Bureau of Statistics (BPS) of Aceh Province and BPS district of West Aceh and local wealth and Revenue Management Office (DPKKD) of West Aceh district. The analysis model used is a simple semi-logarithmic linear model with SPSS. Based on the results of the study obtained that the correlation coefficient (R) of 0.267 where the relationship between PAD with economic growth in this district is still weak. Further coefficient of determination on (R2) amounted 0.71. As for the model of the equivalent Y = 23,584 + 0,094 X + E, with a test value of T is not significant, where the Thit < Ttab. The author recommends that programs from the government are required in an effective method of collecting PAD components, so that their realization value increases that will indirectly affect the economic growth of the district.Keywords: regional taxes, regional retribution and economic growth.